A New Division of Labor Meeting America's Security Challenges Beyond Iraq - Hoehn, Andrew R. (RAND Corporation, 2007)
An emerging U.S. grand strategy--the promotion of democracy and freedom abroad--will certainly involve the U.S. armed forces. Although they must change to meet changes in emphasis and demand, theycannot risk their historic strengths. Some areas of interest are the organization and employment of forces, planning for future conflicts, developing information resources, and fostering partnerships among the services and with allies.